Information and Communication Technology and the Physically Challenged: An Advocacy for an Inclusive Information Society in Nigerian Libraries - Nwaohiri, Ngozi Maria; Emezie, Nkeiru A. (MiddleBelt Journal of Library and Information Science, 2015)
This article discusses the state of the physically challenged in our society. It describes the nature and characteristics of the term ‘physically challenged’. The article emphasizes the role of libraries and information professionals in bridging the gap between the physically challenged and their normal counterparts in the 21st century. It further highlights the various assistive devices that can be provided by libraries to meet the special information needs of the physically challenged. The paper advocates training of librarians in ICT and special education to acquire relevant skills to serve the physically challenged and adequate funding to acquire, maintain and sustain technology.